Make biometric-based person identification system applicable - Teo, Lay Hoon. (2013)
Personal identification and verification are playing more and more important role in the society. Traditional authentication method such as password and smart card, often cannot meet today’s security as they can be easily forgotten, lost or stolen. Biometric technology has appeared as a new solution to these problem. Among all the variable biometric technologies, automatic palmprint verification is an important complement to biometric authentication.